Intensi Orang Tua dalam Pengambilan Keputusan untuk Menikahkan Anak Perempuan di Bawah Usia 20 Tahun di Kecamatan Pakem Kabupaten Bondowoso (Parents Intention in Decision Making to Wed Their Under 20 Years Old Daughter in Pakem, Bondowoso Regency) - Riski Anisa; Andrei Ramani; Irma Prasetyowati (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Early marriage is a marriage which is conducted before the age of 20th. Early married girl hasmore risk in reproductive health and mortality. Bondowoso Regency has the highest of earlymarriage rates 52,93% from the marriage total in 2012. Pakem Subdistrict in BondowosoRegency has the highest rate for marriage under 20 years. In 2013, Pakem Subdistrict inBondowoso Regency has the higest rate of early marriage rates 53,18% and in 2014, earlymarriage rates 67,02%%. This study aimed to identify factors of parents intention on under20 years old girls marriage in Pakem, Bondowoso Regency. This study based on the Theoryof Planned Behavior with cross-sectional design. The respondent were parents which have10-19 years old daughter not married yet. Spearman correlation test applied to determineassociations between each variable. Result showed that knowledge significantly associatedwith attitude (p=0,000), subjective norm (p=0,008), and behavioural control (p=0,000).Income rate of parents was not significantly associated with attitude (p=0,106), subjectivenorm (p=0,951), and behavioural control (p=0,564). Education significantly associated withattitude (p=0,000), subjective norm (p=0,007), and behavioural control (p=0,035). Attitude(p=0,001), subjective norm (0,001), and behavior control (0,000) were significantly associatedwith parents intention.Keywords: early marriage, intention, attitude, subjective norm, behavioral control